PENGARUH KEPEMIMPINAN TRANSFORMASIONAL KEPALA SEKOLAH TERHADAP PENGGUNAAN TEKNOLOGI SEBAGAI SUMBER BELAJAR DI UPT SMAN 9 WAJO - Sulfiani, Besse; Hasanah, Niswayanti; Ambo Upe (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research is motivated by the level of use of technology that still needs to be improved and the use of technology is more demanding than necessary. This study aims to determine the influence of transformational leadership of school principals on the use of information technology as a learning resource at UPT SMAN 9 Wajo. This type of research is a quantitative research, where data is collected through a questionnaire distributed to teachers at UPT SMAN 9 Wajo. The data analysis used was normality test, descriptive analysis, simple linear regression analysis and simple regression coefficient test. The results of the study showed that there was a positive influence between the transformational leadership of the principal and the increase in the use of information technology by teachers as a learning resource by 55% and the level of information technology use at UPT SMAN 9 Wajo was in the good category with a percentage of 45%.